Primary, secondary and tertiary prevention of food allergy: current practices and future directions - Cronin, Caoimhe; Salzberg, Noah; Woon, Yuxin; Trujillo Wurttele, Juan (Allergologia et Immunopathologia, 2023)
The incidence of food allergies has risen around the globe, and experts have been exploring methods of preventing such allergies in young children to ease the burden of disease and reduce the morbidity and mortality caused by anaphylaxis to food allergens. Such preventative measures can be categorised as primary, secondary and tertiary prevention, which are discussed in detail in this review. Primary prevention is defined as the prevention of becoming sensitised towards specific allergens. The evidence suggests that avoiding common allergenic foods during pregnancy and breastfeeding is not protective against food allergies, and guidelines recommend weaning from 4 to 6 months of age, with recent studies supporting the early introduction of peanuts at 4 months to prevent peanut allergy. Secondary prevention targets patients who are already sensitised and aims to halt the progression of sensitisation, with evidence for high rates of success and safety in trials of early introduction to milk and peanuts using oral immunotherapy in sensitised infants. Tertiary allergy prevention focuses on reducing the risk of a patient having anaphylaxis, with oral immunotherapy being the most common method of promoting tolerance in allergic children. Several studies have demonstrated successful reintroduction for milk, egg and peanut; however, no such guidelines are recommended for other foods. Finally, dietary advancement therapy in the form of milk and egg ladders has been employed as a method of primary, secondary and tertiary prevention of allergies, particularly in Ireland, the UK and Canada.